Crop Management Cases and Tools for Higher Yield and Sustainability - Marin, Fabio R. (IntechOpen, 2012)
Agricultural production is related to physical constrains, which may not always be overcomed by technology. However, under the same conditions, it is possible to see well-managed farms consistently making greater profits than similarly structured, neighboring farms. For each abiotical condition, it is well-known there is a difference between the potential and observed yields, which is usually high and often could be reduced through more appropriate management techniques. In this book, we have a selection of agricultural problems encountered in different regions of the world which were addressed using creative solution, offering new approaches for well-known techniques and new tools for old problems.